Love as a central object of study for feminist theory in the 21st Century (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
Heterosexual love relationships have become a central object of study for feminist theory in the 21st century, on the one hand, because of the way they maintain and reproduce gender inequality in a context of democracy, freedom and formal equality, and on the other hand, because of the deep transformations that significances of love and couple have undergone when these values have spread to the intimate sphere. In line with these approaches, this paper analyzes, from the results obtained in a PHD thesis, the possible influence of gender inequality on the perception and resolution of conflicts, expressed by heterosexual persons with respect to their intimate relationships. Research results lead to the conclusion that conflict may be a key question for the analysis of gender inequality as, on the one hand, it is an expression of feminine dissatisfaction generated by the inequalitarian dynamics that take place in the heterosexual intimacy, and on the other hand, because it demands an intervention that tends to reinforce traditional gender roles.
Keywords: Heterosexual couple; gender; conflict; emotional inequality; power; love